Commitment in the Relationship Between Structural Empowerment and Social Work Competency - Ahmad Shuhaimi, Noorhaizah; Mohd Noor, Amna Binti; Mohd Khir, Azlina Binti; Wan Jaafar, Wan Munira Binti (Asian Social Work Journal, 2025)
This study examines the role of commitment as a mediator in the relationship between structural empowerment and social work competency among social workers in the Department of Social Welfare (JKM). Structural empowerment encompasses the provision of opportunities, information, support, and resources by organizations to support the professional development of social workers. This research uses a quantitative approach through a survey method, involving 300 randomly selected respondents. The study instrument includes scales that measure structural empowerment, organizational commitment, and social work competency, which includes knowledge, skills, values, and ethics. Multiple regression analysis and mediation tests show a significant direct relationship between structural empowerment and social work competency (β = 0.402, p < 0.001). Commitment was found to act as a mediator in this relationship, with a significant indirect effect of structural empowerment on competency through commitment (β = 0.105, p < 0.01). The results also indicate that high commitment can reduce burnout and increase social workers' resilience in facing complex challenges. These findings suggest that commitment is a critical element in strengthening the relationship between structural empowerment and social work competency. Therefore, organizations are encouraged to reinforce structural empowerment by providing support, career development opportunities, and a positive work environment. This not only increases social workers' commitment but also helps improve their competency in delivering quality services to the community. This study contributes to the growing literature on the role of commitment in enhancing competency through structural empowerment in social work.